Wernicke’s encephalopathy following radical gastrectomy and prolonged parenteral nutrition: a case report of pyloric obstruction and undisclosed psychiatric comorbidity - Ma, Hanchen; Zhao, Zheng; Zhang, Wenjie; Jin, Shuaichen; Li, Linchuan; Zong, Ruizhao; Fu, Xueyu; Sun, Yingjie; Pan, Yunmiao; Zhu, Jiankang; Zhang, Guangyong (Frontiers in Oncology, 2025)
Wernicke’s encephalopathy (WE), a neuropsychiatric emergency caused by thiamine deficiency, is increasingly recognized in nonalcoholic populations. We present a 64-year-old male with pyloric obstruction from gastric cancer (stage IIIA) who developed WE 20 days after gastrectomy. Prolonged thiamine-free total parenteral nutrition (TPN), delayed enteral intake, and cancer-related hypermetabolism jointly precipitated a thiamine deficiency. Undisclosed psychiatric comorbidity exacerbated diagnostic challenges and potential risk. Despite initial diagnostic challenges, timely neurological assessment and urgent brain MRI confirmed the diagnosis on the day of readmission. Immediate thiamine supplementation led to full neurological recovery. At six-month follow-up, the patient remained neurologically intact with structured dietary and psychological counseling, ensuring sustained psychiatric stability during adjuvant chemotherapy. This novel case of WE following radical gastrectomy, prolonged TPN, and in the context of gastric cancer with pyloric obstruction and undisclosed psychiatric comorbidity, underscores the necessity of multidisciplinary collaboration to optimize perioperative nutritional and psychosocial management in high-risk oncological surgical populations.